Molecular Docking of Active Compounds Piper crocatum on the A-Glucosidase Enzyme as Antidiabetic - Mustika Weni; Mega Safithri; Djarot Sasongko Hami Seno (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Ethanol extract of Piper crocatum leaves has inhibitory activity of α-glucosidase enzyme. Ethyl acetate fraction from Piper crocatum leaves has the highest antioxidant activity. Previous research has provided information that the ethyl acetate fraction of Piper crocatum leaves has an inhibition of α-glucosidase containing 6XO32ZSP1D, Ethyl L-serinate hydrochloride compound, Schisandrin B compound, Columbin compound, 4- (4-methoxy-phenylamino) -2 compound, 3-dihydro-1H-4a, 9-diazacyclopenta (b) fluorine-10-carbonitrile, compound 6-Amino-4- [3- (benzyloxy) phenyl] -3-tert-butyl-2,4-dihydropyrano [2, 3-c] pyrazole-5-carbonitrile, compound 4 - 4.6-Bis [(3R, 5S) -3,5-diamino-1-piperydinyl] -1,3,5-triazine-2-yl amino) benzenesulfonamide and compound 1.1 '- (1,4-butanediyl) bis 2,6-dimethyl-4 - [(3-methyl-1,3-benzothiazol-2 (3H) ylidene) methyl] pyridinium. This study aims to study the interaction between bioactive compounds contained in ethyl acetate fraction of Piper crocatum leaves with α-glucosidase enzyme in In Silico using AutoDock Vina, Columbin shows the lowest binding energy with binding sites with amino acids Ser240, Asp242, His280, Arg315, Glu411, Phe159, Arg442, Tyr158 and Phe303. Columbin has the stability and inhibits the α-glucosidase enzyme from S. cerevisiae better than the seven other compounds, because it has OH and CH3 groups which play a role in the interaction with around the active side of the α-glucosidase enzyme.Keywords: Columbin, In Silico, α-Glucosidase",